The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.3168/jds.s0022-0302(89)79155-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of a Prolonged-Release Formulation of N-Methionyl Bovine Somatotropin in Lactating Dairy Cows

Abstract: Eighty Holstein cows (first, second, or third lactation) were used to evaluate the efficacy of a prolonged-release formulation for sometribove (n-methionyl bovine somatotropin). Cows were fed ad libitum a complete mixed diet and milked twice daily. Cows were allocated randomly by parity to two treatment groups receiving 500 mg sometribove in a prolonged release formulation or excipient at 14-d intervals starting at 60 +/- 3 d postpartum and continuing for 36 wk. Treatment with sometribove increased FCM yield t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 20 publications
5
18
1
Order By: Relevance
“…The pattern of peak milk response at about day 7 of each 14-day injection cycle in experiment 2 was similar to previous data for formulated zinc-[Met',Leu127]-bGH (Bauman et al 1989). Overall response to 500 mg rbGH/14 days (7-8-10-6 kg/day) in this study was similar to the previous 8-10 kg/day response to daily injection (25 mg/day) of solubilized rbGH variants (Eppard et al 1992 arations used in the follow-up study to experiment 2 averaged 1-28 and 1-33 units/mg protein; equiva¬ lent preparations used in the previous study (Eppard et al 1992) each averaged 1-57 units/mg pro¬ tein.…”
Section: Methodssupporting
confidence: 81%
“…The pattern of peak milk response at about day 7 of each 14-day injection cycle in experiment 2 was similar to previous data for formulated zinc-[Met',Leu127]-bGH (Bauman et al 1989). Overall response to 500 mg rbGH/14 days (7-8-10-6 kg/day) in this study was similar to the previous 8-10 kg/day response to daily injection (25 mg/day) of solubilized rbGH variants (Eppard et al 1992 arations used in the follow-up study to experiment 2 averaged 1-28 and 1-33 units/mg protein; equiva¬ lent preparations used in the previous study (Eppard et al 1992) each averaged 1-57 units/mg pro¬ tein.…”
Section: Methodssupporting
confidence: 81%
“…As was the case with the Oldenbroek et al (1989) study, milk yield increases were cyclic within injection intervals in the Bauman et al (1989) trial. Feed intake did not follow the same cyclical pattern, but rather, increased gradually over the first 10 wk in treated cows.…”
Section: Long-term Production Responsesmentioning
confidence: 82%
“…Gross observations reported by some authors indicate no differences between controls and rbST-treated cows for reproductive efficiency Eppard et at. 1988;reviewed by McBride et al 1988;Bauman et al 1989;Oldenbroek et al 1989). These observations have been confirmed by Eppard et al (1987) and Phipps et al (1988), whose combined results indicated normal estrus cycles, number of days to first ovarian activity and correct insemination, pregnancy rates, embryo or fetal loss, premature calving, and calf development of rbST-treated cows.…”
Section: Concerns Of Producersmentioning
confidence: 94%
See 1 more Smart Citation
“…Asimov and Krouze in 1937 first demonstrated injections of pituitary extract increased milk production in dairy cows ( 1). Investigators since then have shown bovine somatotropin regulates metabolic processes resulting in more efficient milk synthesis, greater milk production and increases lean tissue synthesis (2)(3)(4). With the advancement in recombinant DNA technology, production and isolation of bovine somatotropin became commercially feasible.…”
Section: Introduction Foster and Leathermanmentioning
confidence: 97%